Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijerph19159249
|View full text |Cite
|
Sign up to set email alerts
|

Association of Playing Cards or Mahjong with Cognitive Function in Chinese Older Adults

Abstract: Cognitive decline in older adults is a major public health threat. This study aimed to explore the association of participation in cards or mahjong with cognitive function in older adults. A total of 7308 older adults were selected from the 2018 Chinese Longitudinal Healthy Longevity Survey. A modified Mini-Mental State Examination (MMSE) was used to assess cognitive function. The participants were classified according to the frequency of playing cards or mahjong into the “regularly” (R) group, “occasionally” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
1
16
0
1
Order By: Relevance
“…For the three cognitive leisure activities researched in this study, there is also relevant literature support for their independent relationship with cognitive health. It has been found that playing mahjong or cards could maintain and improve cognitive function in older adults [ 22 ] and lower the risk of dementia [ 19 ]. Moderate internet access is not only effective in improving the health of older adults [ 35 ] but also in improving cognitive function and slowing cognitive decline [ 36 , 37 ], possibly through the effect on pallidum volume [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the three cognitive leisure activities researched in this study, there is also relevant literature support for their independent relationship with cognitive health. It has been found that playing mahjong or cards could maintain and improve cognitive function in older adults [ 22 ] and lower the risk of dementia [ 19 ]. Moderate internet access is not only effective in improving the health of older adults [ 35 ] but also in improving cognitive function and slowing cognitive decline [ 36 , 37 ], possibly through the effect on pallidum volume [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are good for avoiding dementia and slowing its progression [ 19 , 20 ]. Such entertainment can also have an impact on life satisfaction, happiness, depression and stress levels [ 21 ], and the frequency of participation is strongly associated with cognitive function and mental health [ 22 , 23 ]. In terms of mortality, some studies have shown that cognitive activity is related to a lower risk of all-cause mortality in older groups [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mahjong is an important and widely popular intellectual game among Chinese people ( 26–28 ). It is a game that demands high cognitive functions ( 26 ). During Mahjong, players need to predict and assess their own and other participants’ moves using cognitive abilities such as visual perception ( 27 ), language comprehension ( 28 ), memory ( 28 ), and judgment to win ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that leisure activities, including physical activity, cognitive activity, intellectual activity, and social activity, are related to a range of better well-being and health outcomes for older people. 11 , 12 , 13 , 14 For instance, Jeong and Park 15 explored the association between participation in leisure activities and quality of life and depression among community-dwelling older adults in Korea, finding that active, emotional, social, and productive activities are positively related to the quality of life and depression. Guerrero Barragán and colleagues’ cross-sectional study of older Colombian adults found that greater participation in cognitive and physical activities in later life was positively associated with cognitive impairment and dementia, independent of literacy and education level.…”
Section: Introductionmentioning
confidence: 99%
“…Successful aging is receiving increasing attention given the dramatic increase in the older adult population. In the past decades, numerous studies have examined the relationship between leisure activity and health and well-being, 11 , 12 , 13 , 14 but little is known about whether leisure activities are associated with successful aging among older people. Furthermore, the prevalence of successful aging is mainly influenced by sex and age.…”
Section: Introductionmentioning
confidence: 99%